Electronic waste management - Eduljee, Gev; Harrison, Roy M., 1948- (Royal Society of Chemistry, 2020)
This new edition provides an updated overview of waste management across the world including new chapters on current issues in recycling and waste management.
Previous edition: 2009.
Keywords: Electronic waste -- Management.; Electronic waste.; elektronické knihy; electronic books